The Effect of Repetition Training in Develop the Physical Fitness and Improve the Sense-Kinetic Perception for the players of Volleyball - Labeeb Zouyan Moseekh (Journal of Global Pharma Technology, 2016)
This study aims at finding out the impact of a Repetition training on developing the kinetic sensory perception of Al-Anbar University players for the academic year 2017-2018, where, (14) player of Volleyball team in college of physical education and sports science_ have been subjected to this training program. The researchers utilize the empirical method depending on the prior and post measurement for one group in order to determine the range of the physical fitness program effectiveness on developing some of the kinetic sensory perception variables. The results show that the conducted program actively affected on the sense of the muscular grip, of time, and of distance which contributes at improving the student's physical fitness level, as well as, at developing the kinetic sensory perception variables. Moreover, the results also show the decreasing of assessment fault of these variables of the sample. The researchers recommend the necessity of emphasizing the importance of physical fitness before the starting the motor skills and using the proposed program for developing the kinetic sensory perception variables.Keywords: Repetition Training, Physical Fitness and Sense-Kinetic Perception.